Evaluation of Weight-Based Dose During Transition From Immediate-Release to Extended-Release Tacrolimus in Kidney Transplant Recipients. (February 2023) - Magid, Mackenzie; Sanoff, Scott; Lee, Hui-Jie; Yang, Zidanyue; Byrns, Jennifer
Background: Manufacturer recommendations for conversion from immediate-release to extended-release tacrolimus, Envarsus XR®, suggests 80% of the total daily dose of the immediate-release formulation. This conversion has not consistently achieved therapeutic levels in the kidney transplant population. Objectives: To determine if a reliable weight-based dosing strategy could be utilized to transition kidney transplant patients from immediate-release to extended-release tacrolimus. This may help establish a safe protocol to guide transition between formulations. Methods: Retrospective, single-center study of adult kidney transplant recipients between July 2015 and December 2018. Excluded patients received dual organs, lacked appropriately drawn tacrolimus levels, or were prescribed interacting medications. Patients were identified by querying prescriptions for extended-release tacrolimus and chart review was performed to exclude any patients without sufficient follow-up after transition. Results: 30 patients who transitioned from immediate-release tacrolimus to tacrolimus XR were included in the final analysis. The median weight-based dose of tacrolimus XR that achieved a therapeutic level among the cohort was 0.158 mg/kg/day (Q1-Q3: 0.0587-0.221), which was about 80% of the original median weight-based immediate-release tacrolimus dose. Therapeutic dosing strategies were widely variable, represented by an R 2 of 0.33 on linear regression. There was a statistically significant difference in median weight-based dosing strategies among patients of various racial backgrounds (p = 0.0148). Conclusions: A weight-based dose of tacrolimus XR could not reliably predict a therapeutic level among the total cohort due to the wide inter-patient variability. The median weight-based rate of conversion from immediate-release to extended-release tacrolimus was 80%.